Greenhouse gas emissions reduction by cross-sector integration of energy systems: Optimal sizing of integrated entities. (15th November 2021) - Li, Ruonan; Mahalec, Vladimir
Highlights: Optimal design of societal infrastructure to minimize greenhouse gas emissions. Integration of energy systems in industries and buildings and electric vehicles. Integrated entities have lower greenhouse gas emissions than individual entities. Minimum greenhouse gas emissions require optimized production schedules. Greenhouse gas emissions reduction is almost constant when optimizing plant sizes. Abstract: Integration of distributed energy systems in residential buildings, commercial buildings, and light industries can decrease greenhouse gas (GHG) emissions further than the lowest emissions achieved by the most efficient standalone system. Until now, an unexplored topic is the optimal relative sizes of the entities in the integrated system. This work introduces a novel optimization model which determines optimal sizes of the entities (buildings and plant capacities) in the integrated system, optimal sizes of the equipment comprising the energy systems, and optimal production schedules. Temperature levels of the heating demands are included in the model to ensure that the heat transfers are feasible. A case study that includes a residential building, a supermarket, a confectionery plant, a bakery plant, a brewery, and electric vehicles is presented. It is shown that the maximum achievable GHG reduction is relatively constant as the sizes of the residential buildings increase, but it requires significant changes in the type and relative sizes of the industrial plants.